Pengaruh Tingkat Risiko Environmental Social Governance (ESG) dan Leverage terhadap Kinerja Perusahaan Pada Indeks IDXESGL Tahun 2020-2022 - Dinda Purwitasari; Sumardi; Meita Larasati (Jurnal Informatika Ekonomi Bisnis, 2023)
This study examines the impact of the ESG risk level and Leverage ratio on the performance of companies included in the IDXESGL index in 2020-2022. This study uses financial reports from companies including the IDXESGL index in 2020-2022 on the Indonesian Stock Exchange in the last 3 years. This type of research is cross-sectional, and the sampling method used is purposive sampling. Descriptive analysis, t-test, correlation, and regression were performed to support the research objectives. SPSS was used for analysis. Based on the regression results, there is no significant effect between the level of ESG risk and company performance. However, there is a significant effect between leverage and company performance. As well as together the risk level of ESG and Leverage have a significant influence on company performance. This research is limited to companies included in the IDXESGL index in 2020-2022 and cannot highlight companies that are not included in the index.